FIGURATIVE LANGUAGE IN SELECTED LOVE-THEMED SONGS IN THE ALBUM "34 NUMBER ONES" BY ALAN JACKSON - Saputra, Wahyudi; Syaputri, Komala Dwi (Premise: Journal of English Education and Applied Linguistics, 2024)
Alan Jackson is a country music singer who has enthusiasm for supporting and maintaining the existence of country music. Figurative language is found in many Alan Jackson songs, which makes it difficult for listeners to understand the meaning of the song lyrics. Country music was feared to disappear since country music fans are mostly adults. Thus, understanding the meaning of figurative language in Alan Jackson songs to avoid misunderstanding the meaning is also the aim of this research. A qualitative method was used while conducting this study, which was considered more suitable to be applied. Eighteen songs have been selected from the album “34 Number Ones” based on love themed. The result showed eighty-six data and thirteen types of figurative language found in the 18 Alan Jackson songs. This study found that the types of figurative language in the eighteen selected Alan Jackson songs appeared as additional words and established a consistent rhythm in the songs. Also, it impacted the meaning that was explained deeply in the songs. Hopefully, this study can provide knowledge of figurative language along with new insights for listeners and be a contribution to further research.